Winter Wheat Absorption Of Nutrients (Npk) From 1 Hectare Of Land And Consumption For 1 Ton Of Grain Yield And Phosphorus Utilization Coefficient - Musurmonova Mukambar Pazitdinovna; Xojimurodov Sunnatilla Boymurod O'g'li; Mirzaxmatova Mahliyo Esonali qizi (Genius Journals, 2023)
In our republic, scientific research aimed at the effective use of mineral fertilizers in increasing the yield of agricultural crops, including wheat, is carried out and certain results are achieved. It is of great practical importance to develop an optimal system of application of mineral fertilizers, ensuring the production of high and high-quality grain crops from autumn wheat varieties in the irrigated typical Boz soils of the Tashkent region, to determine the food environment formed in the soil for specific periods of the autumn wheat development phases and the amount and ratio of Fertilizer is an effective and fast influencing factor that allows you to raise the quality of the crop. The development of an optimal norm for the use of a suspension made of fertilizers in leaf feeding, the study of the influence of these norms on the development of autumn wheat growth, seedling thickness, grain texture and quality in Ham has a special purpose
Keywords: Nitrogen; phosphorus; potassium